2001
DOI: 10.1177/102490790100800208
|View full text |Cite
|
Sign up to set email alerts
|

An Undiagnosed Myasthenia Gravis Presented with Acute Respiratory Failure

Abstract: Acute respiratory failure is an uncommon initial presentation of myasthenia gravis. We present a case of unrecognised myasthenia gravis. She initially presented with dysphonia and was managed by speech therapy and ENT surgeons for a year. The diagnosis was finally made after the patient presented with acute respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In a recent publication from the Mayo Clinic, it was observed that among patients with neuromuscular failure without known diagnosis before admission have poorer outcomes. [4] In this study, nearly a third of all patients admitt ed to the intensive care unit with acute neuromuscular respiratory failure were finally diagnosed with myasthenia gravis; this number was over twice higher than the number of patients who had a fi nal diagnosis of Guillain Barre syndrome. Clearly, the diagnosis of myasthenia gravis should be on the top of the list in a young woman presenting with acute neuromuscular respiratory failure and well-preserved tendon refl exes without any previous history of muscle disease or toxic exposure (e.g.…”
Section: Commentarymentioning
confidence: 67%
See 1 more Smart Citation
“…In a recent publication from the Mayo Clinic, it was observed that among patients with neuromuscular failure without known diagnosis before admission have poorer outcomes. [4] In this study, nearly a third of all patients admitt ed to the intensive care unit with acute neuromuscular respiratory failure were finally diagnosed with myasthenia gravis; this number was over twice higher than the number of patients who had a fi nal diagnosis of Guillain Barre syndrome. Clearly, the diagnosis of myasthenia gravis should be on the top of the list in a young woman presenting with acute neuromuscular respiratory failure and well-preserved tendon refl exes without any previous history of muscle disease or toxic exposure (e.g.…”
Section: Commentarymentioning
confidence: 67%
“…However, our patient did not manifest any prolonged paralysis aft erwards. [4] We tried to determine the cause of respiratory failure. We did not fi nd any evidence of a hypoxemic respiratory failure; there were no definite infiltrations, edema, eff usion, or pneumothorax on chest X-ray.…”
Section: Discussionmentioning
confidence: 99%